Psak 38: Kombinasi Bisnis Entitas Sepengendalian Pada Pencatatan Laporan Keuangan Perusahaan (Jurnal Kendali Akuntansi, 2024)
PSAK 38 is a statement of accounting standards that regulates the accounting for business combinations of entities under common control. PSAK 38 was created to fulfill business combinations based on PSAK 22, with additional arrangements for the entity receiving the business and the entity selling the business. The scope of PASK 38 is regarding forms of business combinations, business combinations under common control, and the presentation and disclosure of company financial reports based on PSAK 38 (revised 2012). The method used in this research uses the literature review method. In addition, the aim of this research is to compare PSAK 38 (revised 2004) with PSAK 38 (revised 2004) in recording company financial statements in general.